2006
DOI: 10.1007/s11423-006-0637-3
|View full text |Cite
|
Sign up to set email alerts
|

A Social-Cognitive Framework for Pedagogical Agents as Learning Companions

Abstract: Teaching and learning are highly social activities. Seminal psychologists such as Vygotsky, Piaget, and Bandura have theorized that social interaction is a key mechanism in the process of learning and development. In particular, the benefits of peer interaction for learning and motivation in classrooms have been broadly demonstrated through empirical studies. Hence, it would be valuable if computer-based environments could support a mechanism for a peer interaction. Though no claim of peer equivalence is made,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(145 citation statements)
references
References 62 publications
6
138
0
1
Order By: Relevance
“…Furthermore, our survey results support the research findings of Steinkuehler and Williams (2006) that interacting within virtual worlds can expose people to a diversity of worldviews and can help them to build a sense of community through the development of virtual social relationships. Additionally, these survey results align with prior research showing that motivation and learning can increase when working with other agents in a virtual environment due to their perceived social relationship (Atkinson et al, 2005;Kim and Baylor, 2006;Mayer et al, 2003;Moreno et al, 2001).…”
Section: Project Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, our survey results support the research findings of Steinkuehler and Williams (2006) that interacting within virtual worlds can expose people to a diversity of worldviews and can help them to build a sense of community through the development of virtual social relationships. Additionally, these survey results align with prior research showing that motivation and learning can increase when working with other agents in a virtual environment due to their perceived social relationship (Atkinson et al, 2005;Kim and Baylor, 2006;Mayer et al, 2003;Moreno et al, 2001).…”
Section: Project Resultssupporting
confidence: 86%
“…Second, research on animated pedagogical agents has shown that agents can increase motivation and learning due to a perceived social relationship between the learner and the agent (Atkinson, Mayer, & Merrill, 2005;Kim and Baylor, 2006;Mayer, Sobko, & Mautone, 2003;Moreno, Mayern, Spires, & Lester, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Emma had the role of a fellow student, rather than a tutor or teacher. This is in line with Bandura's (1997) suggestion of model-target similarity, and also because (non-agent) peer-students have been found to positively influence motivation and learning (Griffin andGriffin, 1998, in Kim andBaylor 2006). Emma's visual appearance was modeled in such a way that she would be a believable peer learner, being of similar age as the participants and looking 'cool'.…”
Section: Learning Environmentsupporting
confidence: 81%
“…These physical appearances seemed to evoke particular emotional responses, such as friendliness, professionalism and a non-threatening approach, which were deemed to be particularly important. These findings are supported by other work in the area, most notably feelings of immersion and the sense of co-presence (Kim & Baylor, 2006). It would seem that choice is essential when seeking to facilitate increased disclosure to a pedagogical agent, particularly in regard to sensitive topics.…”
Section: Solutions and Recommendationssupporting
confidence: 73%